2023
DOI: 10.1145/3617169
|View full text |Cite
|
Sign up to set email alerts
|

Acrobats and Safety Nets: Problematizing Large-Scale Agile Software Development

Knut H. Rolland,
Brian Fitzgerald,
Torgeir Dingsøyr
et al.

Abstract: Agile development methods have become a standard in the software industry, including in large-scale projects. These methods share a set of underlying assumptions that distinguish them from more traditional plan-driven approaches. In this paper we adopt Alvesson and Sandberg's problematization approach to challenge three key assumptions that are prevalent in the large-scale agile literature: 1) agile and plan-driven methods are mutually exclusive; 2) self-managing and hierarchically-organized teams are mutually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…For example, Barlow et al (2011) define the term as characterised by multiple stakeholders and complex projects within large organisations. Rolland et al (2016) suggest that large-scale involves complex integration with various internal and external information systems, multiple stakeholders with different interests. A large-scale agile transformation is an attempt to scale up how development organisations move from small agile practices (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Barlow et al (2011) define the term as characterised by multiple stakeholders and complex projects within large organisations. Rolland et al (2016) suggest that large-scale involves complex integration with various internal and external information systems, multiple stakeholders with different interests. A large-scale agile transformation is an attempt to scale up how development organisations move from small agile practices (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the scaling up of agile methods to a large-scale development setting presents ‘ a thorny set of issues ’ (Reifer et al, 2003), such as the weak assumption about how effective large-scale development can be achieved by simply scaling up small-scale agile methods (Rolland et al, 2016; Carroll et al, 2020). Regardless of the chosen approach of a prescribed scaled method or allowing them to evolve at a team level to implement large-scale methods, it is extremely challenging to successfully scale agile methods (Paasivaara, 2017; Conboy and Carroll, 2019; Uludag et al, 2020; Edison et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations